2009
DOI: 10.1002/pssc.200880782
|View full text |Cite
|
Sign up to set email alerts
|

Novel tunable phosphor‐free white III‐nitride light emitting diodes based on indium rich InGaN nanostructures

Abstract: Phosphor free tunable white light emitting diodes (LEDs) have been fabricated using stacked InGaN/GaN quantum wells (QWs) comprised of a lower set of red emitting QWs with an upper set of blue and green emitting QW layers. With antisurfactant treatment, indium rich InGaN nanostructures are incorporated in the InGaN/GaN quantum well during growth. AFM study shows the formation of InGaN nanostructures with an average diameter of 40‐80 nm in the quantum well layer. This growth technique enables red emitting III‐N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…On other hand, it is noteworthy that, with the development of micro/nanofabrication techniques, the generation of multiple emission wavelengths from micro/nano-structure InGaN LEDs also enables the fabrication of color-tunable LEDs. [7][8][9][10][11] Funato et al successfully demonstrated the fabrication of color-tunable LED emitting with dual-wavelength emission from multifacet QWs. 7,8) Hong et al reported visible-colortunable LEDs fabricated using InGaN/GaN multiple quantum wells (MQWs) formed on GaN nanostructures.…”
mentioning
confidence: 99%
“…On other hand, it is noteworthy that, with the development of micro/nanofabrication techniques, the generation of multiple emission wavelengths from micro/nano-structure InGaN LEDs also enables the fabrication of color-tunable LEDs. [7][8][9][10][11] Funato et al successfully demonstrated the fabrication of color-tunable LED emitting with dual-wavelength emission from multifacet QWs. 7,8) Hong et al reported visible-colortunable LEDs fabricated using InGaN/GaN multiple quantum wells (MQWs) formed on GaN nanostructures.…”
mentioning
confidence: 99%
“…13) All results shown above indicated that we could obtain a white LED and that the existence of its compositional nonuniformity of the InGaN/GaN MQWs active area leads to a more effective carrier trapping at the MQWs. 14) Moreover, we observed a blue shift of the longwavelength area with an increase in 20 to 30 mA. The blue shift of the long-wavelength area can be mainly attributed to the band-filling effect of the localized state in In-rich regions.…”
Section: Resultsmentioning
confidence: 57%
“…Each well consists of a wetting InGaN layer, 1 nm thick grown with TMI flow rate at 24 µmol/min and TMGa at 12 µmol/min, designated as α‐layer. After the growth of the α‐layer, the sample underwent Trimethylindium (TMIn) treatment 7, 8 where TMIn was allowed to flow under NH 3 rich condition for 30 s to form the indium rich InGaN nanostructures before the growth of the InGaN well, the β‐layer. The encapsulated AlN cap layer of ∼1.2 nm thick was then deposited followed by a 10 nm capped GaN layer.…”
Section: Methodsmentioning
confidence: 99%